Combined thoracic paravertebral and pectoral nerve blocks for breast surgery under sedation: a prospective observational case series. (12th January 2018) - Pawa, A.; Wight, J.; Onwochei, D. N.; Vargulescu, R.; Reed, I.; Chrisman, L.; Pushpanathan, E.; Kothari, A.; El‐Boghdadly, K.
Summary: Avoidance of general anaesthesia for breast surgery may be because of clinical reasons or patient choice. There is emerging evidence that the use of regional anaesthesia and the avoidance of volatile anaesthetics and opioid analgesia may have beneficial effects on oncological outcomes. We conducted a prospective observational case series of 16 breast cancer surgeries performed under thoracic paravertebral plus pectoral nerve block with propofol sedation to demonstrate feasibility of technique, patient acceptability and surgeon satisfaction. Fifteen out of 16 cases were successfully completed under sedation and regional anaesthesia, with one conversion to general anaesthesia. Eleven out of 16 cases required low‐dose intra‐operative opioid analgesia. Out of the 15 surgical procedures completed under regional anaesthesia with sedation, all patients experienced either no or minimal intra‐operative pain, and all would choose this anaesthetic technique again. Surgeon‐reported operating conditions were 'indistinguishable from general anaesthesia' in most cases, and surgeons were 'extremely satisfied' or 'satisfied' with the technique after every procedure. Combined thoracic paravertebral plus pectoral nerve block with intra‐operative sedation is a feasible technique for breast surgery.